2008
DOI: 10.1165/rcmb.2007-0198tr
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Epithelial β2-Adrenergic Receptors

Abstract: b 2 -adrenergic receptors are present throughout the lung, including the alveolar airspace, where they play an important role for regulation of the active Na 1 transport needed for clearance of excess fluid out of alveolar airspace. b 2 -adrenergic receptor signaling is required for up-regulation of alveolar epithelial active ion transport in the setting of excess alveolar edema. The positive, protective effects of b 2 -adrenergic receptor signaling on alveolar active Na 1 transport in normal and injured lungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 131 publications
(124 reference statements)
4
78
0
Order By: Relevance
“…Short Time Exposure (5-30 min) to TGF-␤1 Induces a Heterologous Desensitization of the ␤ 2 AR via a PI3K-dependent Mechanism-Several studies have shown that ␤ 2 AR signaling in the distal lung epithelium is mediated by a cAMP-and PKAmediated mechanism (41). We found that exposure to TGF-␤1 significantly inhibited epinephrine-induced cAMP accumulation and PKA activity in rat ATII cell monolayers (Fig.…”
Section: Tgf-␤1 Inhibits ␤ 2 Ar Agonist-stimulated Vectorial Alveolarmentioning
confidence: 63%
See 2 more Smart Citations
“…Short Time Exposure (5-30 min) to TGF-␤1 Induces a Heterologous Desensitization of the ␤ 2 AR via a PI3K-dependent Mechanism-Several studies have shown that ␤ 2 AR signaling in the distal lung epithelium is mediated by a cAMP-and PKAmediated mechanism (41). We found that exposure to TGF-␤1 significantly inhibited epinephrine-induced cAMP accumulation and PKA activity in rat ATII cell monolayers (Fig.…”
Section: Tgf-␤1 Inhibits ␤ 2 Ar Agonist-stimulated Vectorial Alveolarmentioning
confidence: 63%
“…Prolonged exposure to TGF-␤1 had no effect on CPT-cAMP-stimulated Cl Ϫ transport across the apical membrane of ATII cell monolayers (data not shown), indicating that the TGF-␤1 prolonged inhibitory effect on Cl Ϫ transport is not downstream of cAMP generation. Previously published work has shown that cAMP plays a critical role in activating CFTR promoter and mRNA expression in lung epithelial cells (41). Thus, we also hypothesized that TGF-␤1 prolonged exposure to TGF-␤1 would result in a reduction in the PKA-dependent CFTR promoter activity and mRNA expression.…”
Section: Tgf-␤1 Inhibits Camp-stimulated Alveolar Fluid Clearancementioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, the disruption of this chain due to inadequate Na + transport, either because of decreased numbers of transporters or inactivation can lead to retention of fluid in alveolar space (14,15). Beta 2 adrenergic (beta 2 A) receptors are present throughout the lung, including the alveolar airspace, and play a pivotal role for regulation of the active Na + transport in ENaC and Na-KATPase (16). Experimental studies documented the therapeutic role for the beta 2 agonist in the treatment of pulmonary edema by accelerating the clearance of excessive fluid from the alveolar space by increasing the function of epithelial transport proteins (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the Na pump in AFC has been directly demonstrated by increased AFC after overexpression of Na pump subunits (24)(25)(26)(27)(28). b-Adrenergic signaling has been reported to increase transcription and translation of Na pump subunit genes (29) and to mobilize intracellular Na pumps for insertion into the basolateral cell plasma membrane (30), making b-adrenergic signaling a plausible mechanism underlying increased expression of Na pump subunit mRNA and higher ouabain-sensitive ATPase activity observed in C18 KO lungs. These results suggest that elevated b2-adrenergic signaling in C18 KO mice results in increased CFTR, ENaC and Na pump activity, and higher AFC.…”
Section: Increased Afc and B-adrenergicmentioning
confidence: 99%